Liderança partilhada num contexto desportivo : Estudo exploratório de uma equipa de voleibol do nível elite - Maio, Maria Bettencourt da Câmara (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research e CRM